A Comparison of Patient Acceptance of 3 Eye Drop Instillation Aids. Issue 8 (August 2021) - Zhu, Catherine Q.; Sadlak, Natalie; Fiorello, Marissa G.; Lee, Deborah; Desai, Manishi
Abstract : Precis: Patients can be quite amenable to using eye drop instillation aids. We should consider recommending these devices to patients who otherwise struggle with drop instillation and medication adherence. Purpose: The purpose of this study was to compare patient acceptance of 3 commercially available eye drop instillation aids in a diverse tertiary care population. Methods: In this prospective, randomized controlled study, 39 patients being treated with topical antihypertensives were assigned to Arm A (no intervention) or Arm B (AutoDrop, AutoSqueeze, or SimplyTouch). Subjects in Arm B were instructed to administer their eye drop with the assigned drop aid at every use for ~6 weeks. Satisfaction surveys were administered at 3 and 6 weeks, where patients also reported the number of drops missed. Results: Thirty-two of 39 subjects completed study participation and full data analysis. Within this total group, 24 subjects were randomized to drop aids (AutoDrop N=10, AutoSqueeze N=8, SimplyTouch N=6), and 8 were randomized to no drop aid. At the 3 and 6-week timepoints, patients found instillation easier with AutoDrop (70.0%, 60.0%) followed by the AutoSqueeze (62.5%, 75.0%), and lastly SimplyTouch (33.3%, 33.3%). For the AutoSqueeze, the mean number of drops missed with and without the drop aid were significantly different ( P =0.015 at 3 wk, P =0.008 at 6 wk). There was no difference in the mean number of drops missed with the AutoDrop and SimplyTouch at either timepoint. Conclusions: For the AutoDrop and AutoSqueeze groups, over 60% of the patients found the devices helpful and would consider using them long-term. Our results suggest that patients would be amenable to using eye drop instillation aids, although more objective data is needed to determine whether these devices would improve medication compliance and clinical outcomes.